Texture Evaluation of an Acid Activated Interstratified Illite-Smectite - Srasra, E.; Trabelsi-Ayed, M. (Asian Journal of Chemistry, 2010)
The change of the pore structure and the adsorption properties of an interstratified illite-smectite of Tunisia after treatment with 3 M HCI at 0.5, 2, 4, 7 and during 20 h were investigated. The pore size distribution, specific surface areas according to BET method, Va-t plot, Dubinin-Radushkevich equation and f-plot were determined by the nitrogen adsorption. The results show that with the increase of the time treatment, the total pore volume increased, while the maximum value of the specific surface area was attained by the sample treated at 4 h. The difference between the pore structure and the adsorption properties were caused by the structural change and the decomposition of the samples.